Mediterranean diet adherence in pregnant women: results of a survey in North East of Italy. (30th September 2020) - Grillone, L; Castriotta, L; Antinolfi, F; Fasan, J; Cortelazzo, F; Madia, A; Righini, M; Savoia, A; Brusaferro, S; Parpinel, M
Abstract: Background: In literature, few studies evaluated Mediterranean diet (MD) adherence in pregnant women, so we decided to conduct a survey to analyze MD and healthy habits in pregnant women living in North East of Italy, in 2018. Methods: In our monocentric observational study, we enrolled >18 years pregnant women (2nd-3rd trimester) to evaluate MD adherence through "PREDIMED" validated questionnaire. Based on previous studies on MD score, women were classified into High-MD adherence (score >8; range 0-14) and low-MD adherence group (score ≤ 8). Comparisons between groups were performed using a t-test, Wilcoxon-Mann-Whitney test, chi square test and regression models as appropriate. We also investigated BMI (body mass index) and healthy habits before and during pregnancy. Results: We analyzed 113 questionnaires and MD score, ranging from 3 to 13, had a mean value of 8.04 (SD 1.95), with low MD adherence in 63% (71) of our sample. Women (mean age 32 years; min 22- max 43; SD 1.95) were mostly employed (95; 84%) and alcohol consumers before pregnancy 79 (70%), especially wine 53 (47%). 5 (4%) didn't quit smoking while pregnant. Comparing BMI data before and during pregnancy to international recommendations, we found inadequate weight gain for each BMI category (100% in underweight, 70.7% in normal weight, 35% in overweight, 50% in obese range). Age was associated with MD adherence (β 0.11; 95%CI 0.04-0.17). Employment was also positively associated with higher MD values (p 0.002). Wine assumption before pregnancy was statistically significant associated with high MD group (p 0.0334). Conclusions: In our study we found MD adherence levels lower than expected and an inadequate weight gain during pregnancy. MD seems also to be age and employment-related. Wine consumption before pregnancy and its positive association with MD need to be further analyzed. Key messages: Mediterranean Diet adherence among pregnant women studied is not high and weight gain is frequently inadequate. Age and employment status might influence MD adherence in pregnancy.